IMPLEMENTATION OF INCENTIVE PRODUCT MARKETING STRATEGY MELALI BALI DMC IN INCREASING SALES VOLUME - I Wayan Winarta; I Gusti Made Wendri; I Ketut Sutama (Journal of Applied Sciences in Travel and Hospitality, 2018)
This study aims to determine the implementation of Incentive Product Marketing Strategy Melali Bali DMC In Increasing Sales Volume. Data collection in this research through interview method, observation and literature study. Melali Bali DMC is one of the companies engaged in the tour and incentive event, in the development of Melali Bali DMC company from the beginning of standing up to now can not maximize in tingka handling events and sales of products owned. The marketing strategy implemented in a company is crucial in the level of product sales for the company, by choosing and using the right strategy in the operation will help the Melali Bali DMC company to increase its sales volume that has not been upgraded. The analysis technique used in this research is Qualitative Descriptive analysis technique, Internal Strategy Factor Matrix, External Strategy Factor Matrix, SWOT Matrix. The results of this study indicate that there is still much that must be addressed in Melali Bali DMC companies to be better diantarnya: Improving the quality of control in the equipment used also in the quality of products provided, Fix and re-creation of products owned, Increase the intensity of relationships with colleagues in market areas and other parties, Increase promotions using web and social media that has been owned and Increase the number of employees also create employee standards and create a creative team.